2016
DOI: 10.1089/ten.tea.2015.0310
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Tension-Controlled Matrices with Osteogenic and Vasculogenic Cells for Vascularized Bone Regeneration In Vivo

Abstract: Despite recent progress, segmental bone defect repair is still a significant challenge in orthopedic surgery. While bone tissue engineering approaches using biodegradable matrices along with bone/blood vessel forming cells offered improved possibilities, current regenerative strategies lack the ability to achieve vascularized bone regeneration in critical-sized/segmental bone defects. In this study, we introduced and evaluated a two-pronged approach for vascularized bone regeneration in vivo. The goal was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…An ongoing challenge for tissue-engineering applications is the sufficient vascularization of an engineered construct that is essential for the survival of the implant and an adequate wound repair. Therefore, the generation of a tissue-like vascularized scaffold for implantation using cell-based prevascularization strategies in different experimental settings has been documented as advantageous (Amini, Xu, Chidambaram, & Nukavarapu, 2016;Grellier et al, 2009;Rouwkema et al, 2006;Tabata et al, 1999). In the context of bone tissue engineering, co-culture systems consisting of endothelial cells and osteoblasts or their precursors can be used from different sources in scaffold-free approaches as well as in combination with a material or co-implanted in Matrigel®-plugs (Fuchs, Jiang, et al, 2009;Rouwkema et al, 2006;Stahl et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…An ongoing challenge for tissue-engineering applications is the sufficient vascularization of an engineered construct that is essential for the survival of the implant and an adequate wound repair. Therefore, the generation of a tissue-like vascularized scaffold for implantation using cell-based prevascularization strategies in different experimental settings has been documented as advantageous (Amini, Xu, Chidambaram, & Nukavarapu, 2016;Grellier et al, 2009;Rouwkema et al, 2006;Tabata et al, 1999). In the context of bone tissue engineering, co-culture systems consisting of endothelial cells and osteoblasts or their precursors can be used from different sources in scaffold-free approaches as well as in combination with a material or co-implanted in Matrigel®-plugs (Fuchs, Jiang, et al, 2009;Rouwkema et al, 2006;Stahl et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A remaining challenge of BTE implants is limited diffusion, which results in the accumulation of material degradation products at the implant core. Consequently, acidic byproducts, such as those associated with PLGA, can cause minimum cellularity at the scaffold core resulting in bone formation that is limited to the periphery of the implant . Our results have demonstrated that the natural polymer based CA and CAc 3D‐porous microstructures and micro‐nanostructures showed greater tissue infiltration in contrast to PLGA structures.…”
Section: Discussionmentioning
confidence: 76%
“…The uptake of Dil‐Ac‐LDL and binding of FITC‐UEA‐1 were examined using fluorescence microscope (EVOS FL Auto, Life Technologies). Immunofluorescence staining of endothelial markers for VEGF receptor‐2 (VEGFR2; ab39256, Abcam) and von Willebrand Factor (vWF; ab6994, Abcam) were also used to characterize EPCs …”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining of endothelial markers for VEGF receptor-2 (VEGFR2; ab39256, Abcam) and von Willebrand Factor (vWF; ab6994, Abcam) were also used to characterize EPCs. 21…”
Section: Isolation and Characterization Of Epcsmentioning
confidence: 99%